FEASIBILITY OF GROWING CURING VARIETIES OF BEANS IN THE CONDITIONS OF WESTERN FOREST STEPPE - Dudchak , T.V.; Duganets, V.I.; Vilchynska , D.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
With the global COVID-19 crisis sweeping across the world and already affecting the food and agriculture sectors, FAO is calling on countries to meet the urgent food needs of their vulnerable populations. After analyzing the problems, it is proposed to introduce into production the climbing bean (Phaseolus multiflorus Wild) and the feasibility of its cultivation on small farms.It made a detailed description of morphological traits on the contrast, uniformity and stability of the individual organs of plants "Sokilchanka" varieties and "Dnistrovka". This bean cultivation technology involves the use of many-support systems of plants. In the absence of such support means shortage of the crop reaches 50% or more, therefore analyzed different designs that have been used to support the plant, on the basis of these researches the optimal harness for climbing beans forms, and its testing carried out by the State Department of Intellectual Property Ministry of Education of Ukraine. These results of phenological observations, which are the technological landmarks timely planting, agro-holding for the care of plants, determining the best timing of harvesting, as a method for growing beans winding does not provide for mechanical harvesting.Recommended technological complex of growing beans winding for farms and gardens is an agro-ecological, with a yield of up to 5 t / ha.